The Analysis of Entrepreneurial Intention of Student’s Economic Education Through the Influence of Digital Business Education - Ikhsananto, Aan; Farliana, Nina; Raharjo, Teguh Hardi (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Entrepreneurship is one of the essential things for the economy in a country to increase the success of development in a country. However, college graduates look for jobs that match their field of expertise, and only a few become entrepreneurs. Students classified as Gen Z have great potential to move into the entrepreneurial sector. Therefore, Gen Z is the main target in developing entrepreneurial interest in Indonesia. This study aims to analyze the effect of Self-Efficacy and Social Media on Entrepreneurial Intention, with Digital Business Education as a mediator. Self-efficacy triggers the emergence of individual trust in becoming entrepreneurs; social media influences entrepreneurial interest. Digital Business Education is seen as a mediator variable in the relationship between variables. This study is an ex post facto study with a quantitative research approach and a causal correlational design. The study subjects were Economic Education students who had taken Digital Business Education. The results of the analysis show that self-efficacy and social media directly influence digital business education; entrepreneurial intention is directly influenced by self-efficacy. However, it was found that Social Media and Digital Business Education did not directly influence Entrepreneurial Intention. Digital Business Education as an intervening variable does not have a role in mediating. Other factors need to be explored further to determine students’ entrepreneurial intentions.